Wild herbivores enhance resistance to invasion by exotic cacti in an African savanna. (27th October 2022) - Wells, Harry B. M.; Crego, Ramiro D.; Alston, Jesse M.; Ndung'u, S. Kimani; Khasoha, Leo M.; Reed, Courtney G.; Hassan, Abdikadir A.; Kurukura, Samson; Ekadeli, Jackson; Namoni, Mathew; Stewart, Peter S.; Kimuyu, Duncan M.; et al.
Abstract: Whether wild herbivores confer biotic resistance to invasion by exotic plants remains a key question in ecology. There is evidence that wild herbivores can impede invasion by exotic plants, but it is unclear whether and how this generalises across ecosystems with varying wild herbivore diversity and functional groups of plants, particularly over long‐term (decadal) time frames. Using data from three long‐term (13‐ to 26‐year) exclosure experiments in central Kenya, we tested the effects of wild herbivores on the density of exotic invasive cacti, Opuntia stricta and O. ficus‐indica (collectively, Opuntia ), which are among the worst invasive species globally. We also examined relationships between wild herbivore richness and elephant occurrence probability with the probability of O. stricta presence at the landscape level (6150 km 2 ). Opuntia densities were 74% to 99% lower in almost all plots accessible to wild herbivores compared to exclosure plots. Opuntia densities also increased more rapidly across time in plots excluding wild herbivores. These effects were largely driven by megaherbivores (≥1000 kg), particularly elephants. At the landscape level, modelled Opuntia stricta occurrence probability was negatively correlated with estimated species richness of wild herbivores and elephant occurrence probability. On average, O. stricta occurrence probability fell from 0.56 to 0.45 as wild herbivore richness increased from 6 to 10 species and fell from 0.57 to 0.40 as elephant occurrence probability increased from 0.41 to 0.84. These multi‐scale results suggest that any facilitative effects of Opuntia by wild herbivores (e.g. seed/vegetative dispersal) are overridden by suppression (e.g. consumption, uprooting, trampling). Synthesis . Our experimental and observational findings that wild herbivores confer resistance to invasion by exotic cacti add to evidence that conserving and restoring native herbivore assemblages (particularly megaherbivores) can increase community resistance to plant invasions. Abstract : Our experimental and observational findings that wild herbivores confer resistance to invasion by exotic cacti add to evidence that conserving and restoring native herbivore assemblages (particularly megaherbivores) can increase community resistance to plant invasions. Photo credit: Gustavo Lozada (same for potential cover image). Resumen: Entender si los herbívoros silvestres confieren resistencia biótica a las invasiones biológicas dadas por plantas exóticas sigue siendo una pregunta clave en ecología. Existe evidencia de que los herbívoros silvestres pueden impedir el proceso de invasión por parte de pantas exóticas, pero no está claro si o como este proceso se generaliza a través de ecosistemas con diferente diversidad de especies de herbívoros silvestres y grupos funcionales de plantas, particularmente en el largo plazo (décadas). Usando datos de tres experimentos de exclusión a largo plazo (de 13 a 26 años) en Kenia central, testeamos los efectos de la presencia de herbívoros silvestres en la densidad de especies de cactus invasores exóticos, Opuntia stricta y O. ficus‐indica (colectivamente, Opuntia ), los cuales se encuentran entre las especies invasoras más dañinas a nivel mundial. También examinamos las relaciones espaciales a nivel de paisaje (6150 km 2 ) entre la riqueza de herbívoros silvestres y la probabilidad de ocurrencia de elefantes con la probabilidad de presencia de O. stricta . Las densidades de Opuntia fueron entre un 74% y un 99% más bajas en casi todas las parcelas accesibles a los herbívoros silvestres en comparación con las parcelas que excluían los mismos. Las densidades de Opuntia también aumentaron más rápidamente en el tiempo en las parcelas que excluían a los herbívoros silvestres. Estos efectos estaban dados en gran medida por la presencia de megaherbívoros (≥1000 kg), en particular los elefantes. A nivel de paisaje, la probabilidad de ocurrencia de O. stricta estuvo negativamente correlacionada con la riqueza estimada de especies de herbívoros silvestres y la probabilidad de ocurrencia de elefantes. En promedio, la probabilidad de ocurrencia de O. stricta se redujo de 0, 56 a 0, 45 con un aumento de la riqueza de herbívoros silvestres de 6 a 10 especies y se redujo de 0, 57 a 0, 40 con un aumento de la probabilidad de ocurrencia de elefantes de 0, 41 a 0, 84. Estos resultados en diferentes escalas espaciales sugieren que cualquier efecto facilitador de Opuntia por parte de los herbívoros silvestres (p. ej., dispersión de semillas/vegetación) es contrarrestado por la supresión (p. ej., consumo, desarraigo, pisoteo). Síntesis . Nuestros resultados experimentales y observacionales de que los herbívoros silvestres confieren resistencia a la invasión de los cactus exóticos se suman a la evidencia de que conservar y restaurar ensambles de herbívoros nativos (particularmente megaherbívoros) puede aumentar la resistencia de las comunidades biológicas a las invasiones de plantas. Muhtasari: Uwezo wa wanyama pori walao mimea kudhibiti uvamizi wa mimea ya kigeni bado ni swali kuu katika ikolojia. Kuna ushahidi kwamba wanyama pori walao mimea wana uwezo wa kuzuia uvamizi wa mimea ya kigeni, lakini haijulikani iwapo inafanyika na jinsi inavyofanyika kwa ujumla katika mifumo ya ikolojia yenye aina mbalimbali ya wanyama pori na vikundi vitendakazi vya mimea, hasa kwa muda mrefu (wa muongo). Kwa kutumia data kutoka kwa majaribio matatu ya muda mrefu (miaka 13 hadi 26) yaliyomo Kenya ya kati, tulipima athari za wanyama pori kwenye wiani wa cactus vamizi za kigeni, Opuntia stricta na O. ficus‐indica (kwa pamoja, Opuntia ), ambazo ni miongoni mwa spishi vamizi zaidi duniani. Pia tulichunguza uhusiano kati ya utajiri wa aina za wanyama pori na uwezekano wa kutokea kwa O. stricta katika kiwango kikubwa cha mazingira (6150 km 2 ). Wiani wa Opuntia ulipunguka kwa kati ya 74% na 99% katika takriban viwanja vyote vinavyofikiwa na wanyama pori walao mimea na uliongezeka kwa kasi zaidi katika viwanja ambavyo havijumuishi wanyama pori walao mimea. Athari hizi zilichangiwa kwa kiasi kikubwa na wanyama walao mimea ambao ni wakubwa sana (≥1000 kg), hasa tembo. Katika kiwango kikubwa cha mazingira, uwezekano wa kutokea kwa Opuntia uliwiana hasi na makadirio ya utajiri wa aina za wanyama pori walao mimea na uwezekano wa kutokea kwa tembo. Kwa wastani, uwezekano wa kutokea kwa Opuntia stricta ulipungua kutoka 0.56 hadi 0.45 kwani utajiri wa aina za wanyama pori walao mimea uliongezeka kutoka spishi 6 hadi 10 na ulipungua kutoka 0.57 hadi 0.40 kwani uwezekano wa kutokea kwa tembo uliongezeka kutoka 0.41 hadi 0.84. Matokeo haya ya viwango mbalimbali yanapendekeza kwamba athari zozote za uwezeshaji wa Opuntia na wanyama wa pori walao mimea (k.m. utawanyishaji wa mbegu/mimea) huzidiwa na ukandamizaji (k.m. kuliwa, kung'olewa, kukanyagwa). Usanisi . Matokeo ya majaribio na uchunguzi wetu kwamba wanyama pori hudhibiti uvamizi wa cactus za kigeni yanachangia ushahidi kwamba kuhifadhi na kurejesha mikusanyiko ya wanyama walao mimea wa asili (hasa wale wakubwa sana) kunaweza kuongeza udhibiti wa jumuiya ya kibayologia dhidi ya uvamizi wa mimea.